Exchange rate exposure in large non financial firms in Malaysia: a test of refinement approach / Imbarine Bujang and Jaratin Lily - Bujang, Imbarine; Lily, Jaratin (Division of Research and Industry Linkages, 2017)
The purpose of this study is to analyse the foreign exchange rate exposure of large non-financial firms in Malaysia before and after adjusting for the thin trading phenomenon from July 2005 to December 2016. The impact of the changes in exchange rates (Malaysia main trading partner's currencies: CNY, SGD and USD) on firms' abnormal returns is examined on 16 total firms (Constituents firms from Bursa Malaysia FTSE 30 Index). This study applies the Dimson-Fowler-Rorke (DFR) method to calculate the adjusted market return beta before incorporating it in the exchange rate exposure empirical model in order to capture the true value of the beta estimators. Autoregressive Distributed Lag (ARDL) method is applied to capture the long run exchange rate exposure. The empirical analysis reveals that most of the securities have the biased market beta, where the value is not equal to one. Furthermore, the diagnostic test reveals both unadjusted and adjusted exposure model tends to have less problematic in error terms if the market beta estimator near to one. Interestingly, the percentage of exposed firms were increased from less than 35% into 50% when DFR beta were applied in the exchange rate exposure model. These findings suggest that the importance of getting the true value of the market beta in order to have a more reliable exposure model especially for markets that experience the thinness trading to help the affected parties (e.g. Financial managers, portfolio managers, investors and policymakers) in their decision making to prepare proper hedging strategies to mitigate the negative impact of the exchange rate movements. The empirical evidence supports the view that Malaysian firms' value are affected by foreign exchange rate exposure and how the thin trading